The Role of Ubiquitin C-Terminal Hydrolase L1 in Renal Function and Glomerular Disease - Boisvert, Naomi (Université d'Ottawa / University of Ottawa, 2017)
Ubiquitin C-terminal hydrolase L1 is a deubiquitinating enzyme that salvages ubiquitin from substrates and maintains intracellular ubiquitin pools. While the role of ubiquitin C-terminal hydrolase L1 is well characterized in neurons, there is an increasing scope of evidence to suggest that ubiquitin C-terminal hydrolase L1 also plays a role in renal function and glomerular disease, however, its specific role in these settings remains incompletely elucidated. In the present thesis we explored the role of ubiquitin C-terminal hydrolase L1 in a mouse model of glomerular disease, ACTN4-associated focal segmental glomerulosclerosis and the role of ubiquitin C-terminal hydrolase L1 in renal function. Deletion of ubiquitin C-terminal hydrolase L1 in a mouse model of ACTN4-associated focal segmental glomerulosclerosis significantly improved indices of podocyte injury, a likely result of ubiquitin pool attenuation and sustained α-actinin-4 levels. However, global ablation of ubiquitin C-terminal hydrolase L1 in mice led to altered renal hemodynamics, namely glomerular hyperfiltration, most likely attributed to nerve dysfunction and loss of arterial resistance. Finally, mice lacking ubiquitin C-terminal hydrolase L1 exhibited perturbations in phosphate homeostasis as these showed evidence of hyperphosphatemia and phosphaturia, indicating altered renal phosphate balance. Altogether, these data show that while ubiquitin C-terminal hydrolase L1 plays a maladaptive role in glomerular disease, it also functions as a crucial regulator of renal hemodynamics and renal phosphate handling, suggesting that it may have distinct functions in diseased and non-diseased kidneys.
Keywords: UCHL1; UCH-L1; hyperfiltration; phosphate; alpha-actinin-4; kidney; glomerular disease